2020
DOI: 10.1161/circinterventions.119.008782
|View full text |Cite
|
Sign up to set email alerts
|

Are Higher Operator Volumes for Unprotected Left Main Stem Percutaneous Coronary Intervention Associated With Improved Patient Outcomes?

Abstract: Background: The relationship between operator volume and survival after unprotected left main stem percutaneous coronary intervention (uLMS-PCI) is poorly defined. Methods: Data from the British Cardiovascular Intervention Society national PCI database were analyzed for all uLMS-PCI procedures performed in England and Wales between 2012 and 2014 and 4 quartiles of annualized uLMS-PCI volume (Q1–Q4) generated. Individual logistic regressions were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Therefore, volume seems important in improving the outcome post rotational atherectomy. Other studies also showed a relationship between volume and outcome in complex procedures [17,18].…”
Section: Cardiac Interventionsmentioning
confidence: 89%
“…Therefore, volume seems important in improving the outcome post rotational atherectomy. Other studies also showed a relationship between volume and outcome in complex procedures [17,18].…”
Section: Cardiac Interventionsmentioning
confidence: 89%
“…39 , 40 Moreover, studies of operator volumes and long‐term outcomes in the United Kingdom have shown conflicting results for HR‐PCI overall as compared with a smaller subset of left main intervention procedures. 41 , 42 Physicians performing HR‐PCI in this study had an average of 9 years of experience after fellowship, and although interventionalists using a multioperator strategy worked at centers with higher annual HR‐PCI volumes, lead operators performed a similar number of HR‐PCI procedures per year compared with their single‐operator peers. These observations suggest that operators in this study may have developed a substantial body of experience with complex PCI, potentially negating the benefits of a second operator.…”
Section: Discussionmentioning
confidence: 99%
“…LM‐PCIs from sites with a predominant access site preference (> 90% or < 10% TRA LM‐PCI) were excluded to minimize any unmeasurable bias for a particular access site preference that could not be accounted for, and to allow comparison between groups where selection of access site was not driven by site‐wide preference. Similarly, low‐volume LM‐PCI sites (< 10 LM‐PCIs during the 10‐year study period) were excluded to minimize influence of an observed volume‐outcome relationship in LM‐PCI 15 . Patients with missing baseline clinical variables (body mass index [BMI] or international standardized ratio [INR] value) were also excluded.…”
Section: Methodsmentioning
confidence: 99%